DESCRIPTIVE PRAGMATIC CONSTRUCTION (Neo Scientific Peer Reviewed Journal, 2023)
This article will talk about the emergence of descriptive linguistics and the history of the origin of descriptivism, the development of linguistic pragmatics from the content of linguistic semantics.